Reply to Berlanga et al. (DOI 10.1515/cclm-2014-0420) - Joannes F.M. Jacobs; Rein M.J. Hoedemakers; Henk te Velthuis (Clinical Chemistry and Laboratory Medicine (CCLM), 2014)
Objectives Preanalytical errors account for approximately 60-70 % of all laboratory errors, with sample misidentification among the most frequent causes of inaccurate and unreliable test results. Pre-barcoded tubes (PBTs) are collection tubes uniquely identified during manufacturing with machine-readable labels, eliminating the need for manual labeling or barcode printing. This study aimed to evaluate the impact of PBTs implementation on preanalytical workflow efficiency. Methods An anonymous online survey comprising 25 questions was distributed to 58 laboratories using PBTs in routine practice. The questionnaire captured demographic data as well as information on workflow changes, including full-time equivalent (FTE) requirements, turnaround time (TAT), and challenges encountered before, during, and after implementation. Results A total of 44 responses (75.9 %) were received within four weeks. More than half of respondents processed up to 5,000 PBTs daily. Implementation of PBTs was associated with reduced sample misidentification rates and shorter TAT in over 80 % of laboratories. These improvements were primarily attributed to the elimination of manual labeling steps, faster automated sample registration, and enhanced integration with digital workflows, resulting in estimated time savings of 1-3 h per day. Additional benefits included reduced FTE requirements and fewer laboratory errors. During implementation, 67 % of laboratories reported resistance, mainly related to adaptation to new processes (43 %) and digital solutions (27 %); however, more than half completed the transition within one month. Conclusions From the user perspective, PBTs implementation improves labeling safety and operational efficiency, reduces error rates, and supports streamlined, digitalized preanalytical workflows.